Procedural peculiarities of the consideration by courts of cases related to the appeal of actions of state bodies and officials in the field of land legal relations - Skobelev, Vladimir P. (Journal of the Belarusian State University. Law, 2019)
The features of the consideration by courts of cases related to the appeal of actions of state bodies and officials in the sphere of land legal relations are analyzed. The analysis is conducted in relation to both civil and economic legal proceedings. The author examines the distribution of cases between the civil and economic process, objects of appeal, the subject of protection, the requirements for documents filed with the courts, time limits for going to court, etc. On this basis, suggestions were made to improve legislation and law enforcement practice.